Glycerol Acetylation: Effect of Graphene Oxide Catalyst Mass Percentage on Glycerol Conversion and Acetin Selectivity - Nur Hidayati; Eggy Juan Prasetyo; Wahyu Annisa Mega Brilianti; Herry Purnama; Malik Musthofa; Anisa Ur Rahmah (CHEMICA: Jurnal Teknik Kimia, 2023)
Glycerol, a byproduct of the transesterification reaction has a wide range of applications. Acetylation is a promising method for converting surplus glycerol into mono-, di-, and tri-acetin, which is used in the cosmetic, pharmaceutical, polymer, and fuel additive sectors. The kind of catalyst and reaction conditions influence glycerol conversion and acetylation selectivity. Acetylation of glycerol was performed in this study by reacting acetic acid and glycerol with a graphene oxide catalyst produced using the Hummers method. The amount of graphene oxide catalyst (3%, 5%, and 7%) in the reaction mixture was adjusted to see how it affected glycerol conversion and reaction product selectivity. Other variables such as the glycerol:acetic acid mole ratio of 1:9, reaction temperature of 120oC, stirring speed of 1000 rpm, and reaction time of 120 minutes were held constant. Glycerol conversion improves with increasing catalyst mass in the reaction mixture, with the highest conversion (92.1%) achieved when employing a 7% catalyst mass, with its selectivity to monoacetin, diacetin, and triacetin being 70.2%, 4.2%, and 25.6%, respectively.